Protein corona of magnetic PEI/siRNA complex under the influence of a magnetic field improves transfection efficiency via complement and coagulation cascades. Issue 26 (12th June 2019) - Jiang, Peipei; Zhu, Yue; Kang, Ke; Luo, Bin; He, Jing; Wu, Yao
Abstract : Magnetic fields enhance the silencing efficiency via the alteration of protein corona adsorbed on magnetic PEI/siRNA complex. Abstract : Magnetic nanoparticles as gene vectors on exposure to a magnetic field enable the efficient enhancement of both transfection efficiency and targeting. However, once vectors are employed in vivo, transfection often fails due to the significant reduction in transfection efficiency, but its underlying mechanism is still not clear and needs to be further explored. Herein, we prepared a gene vector (polyethylenimine modified by stearic acid-superparamagnetic iron oxide, stPEI–SPIO) via the encapsulation of high-quality superparamagnetic iron oxide nanoparticles (SPIONs) by stearic acid-modified polyethylenimine (PEI) and examined its silencing efficiency in normal cells (mouse fibroblast cells expressing green fluorescent protein, GFP-3T3 cells) and cancer cells (human breast cancer cells expressing green fluorescent protein, GFP-MCF-7 cells) in the presence and absence of a magnetic field. The results demonstrated that the presence of a magnetic field accelerated cellular uptake and improved the silencing efficiency in the presence of fetal bovine serum (FBS), which is possibly due to the alteration of the composition and amount of protein corona. On the one hand, the amount of proteins related to adenosine triphosphate (ATP) binding, the cytoskeleton and the complement and coagulation cascades increased under the influence of a magnetic field, resulting in the acceleration of the cellular uptake of the stPEI–SPIO/silencing RNA (stPEI–SPIO/siRNA) complex and enhancement in the transfection efficiency. On the other hand, the amount of proteins related to endocytosis, especially the major histocompatibility complex (MHC) and heat shock proteins, was reduced, which weakened the rejection of the nanocomplex by cells. Furthermore, the complement and coagulation cascade pathway was directly involved in the cellular uptake. The complement component C3 in vitro model results further corroborated that the critical activation of the complement and coagulation cascade pathway enhanced the transfection efficiency. This study not only offers mechanistic insights into the magnetic field enhancement in transfection efficiency, but also provides an important reference for the design of gene vectors and their utilization in clinic.